Boric Acid Radiolysis in Primary Coolant Water of PWR at Temperature of 250oC - Geni Rina Sunaryo (Jurnal Pengembangan Energi Nuklir, 2017)
BORIC ACID RADIOLYSIS IN PRIMARY COOLANT WATER OF PWR AT TEMPERATURE OF 250oC. The existence of oxygen in the primary coolant system of PWR could lead to corrosion, hence it is very important to suppress the oxygen concentration in the system. Therefore, study of the effect of boric acid addition into the primary coolant water system of PWR to suppress oxygen concentration resulted from gamma-ray radiation is essential to be performed. The aim of this research is to understand reaction mechanism at temperature of 2500C and the effect of boric acid adding toward oxygen concentration in the PWR primary coolant water. Methodology used is simulation using Facsimile software. Input for the software namely radiolysis reaction mechanism for pure water, G value from radiolysis product, dose rate of 1 and 104 Gy/s, aeration and deaeration system, and specific reaction of boric acid with hydroxyl radical and hydrated electron at temperature 250C and 3000C. The output are in the form of irradiation time vs oxygen concentration time series. The results show that the oxygen production increase significantly with the irradiation time and reach the saturated concentration at 107s. Based on the plot of oxygen’s concentration at 107s vs boric acid, several results are as following: oxygen concentration significantly suppressed by boric acid addition and gives the exponential decreasement, the higher dose rate gives the higher concentration of oxygen, the aeration system gives no effect on suppressing oxygen concentration at boric acid addition up to 0.1M.